Relevant Context, Genuine Relation: Genre, Form, and Gender in Twenty-First Century The Winter's Tale Criticism. Issue 1 (May 2020) - Martin, Thomas L.
Abstract : A resurgence of interest in Shakespeare's late romances has scholars once again asking what kind of work is The Winter's Tale . After The Tempest, it has occupied critics over the first two decades of the twenty-first century more than any other in this group of late plays. Besides a variety of new themes, dramatic material, staging challenges, and interpretive cruxes, the question of genre among these plays still puzzles late modern critics as much as it did early Enlightenment critics. What was Shakespeare doing experimenting with genre so late in his career, where elements of tragedy and comedy seem to flow together to create a hybrid form or introduce something new on the stage? This article considers how new approaches to The Winter's Tale parallel new speculations about its genre and decisions about its performance on stage. Considering how the issue of genre operates as a kind of regulative principle over new interpretations in much the same way that stage productions must make the play coherent in a limited physical space for an evening's entertainment, the article makes a case for preserving the work's central and traditionally celebrated wonder.